2017
DOI: 10.5935/0946-5448.20170018
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Subjective Tinnitus with Neuro-Cognitive Performance

Abstract: Introduction: Chronic subjective tinnitus is associated with cognitive disruptions affecting perception, thinking, language, reasoning, problem solving, memory, visual tasks (reading) and attention. Objective: To evaluate existence of any association between tinnitus parameters and neuropsychological performance to explain cognitive processing. Materials and Methods: Study design was prospective, consisting 25 patients with idiopathic chronic subjective tinnitus and gave informed consent before planning their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…As shown previously, the more severe the tinnitus, the more likely the deterioration of cognitive processing is, suggesting that cognitive processing speed is an independent predictor of tinnitus severity [12]. Furthermore, a neuropsychological study reported a significant negative correlation between tinnitus loudness and duration, and performance on neurocognitive tasks [15]. In this regard, the increase in tinnitus severity may negatively affect attentional orientation and executive control, reducing cognitive processing speed [6].…”
Section: The Impact Of Tinnitus Severity On MCI Presencementioning
confidence: 75%
See 4 more Smart Citations
“…As shown previously, the more severe the tinnitus, the more likely the deterioration of cognitive processing is, suggesting that cognitive processing speed is an independent predictor of tinnitus severity [12]. Furthermore, a neuropsychological study reported a significant negative correlation between tinnitus loudness and duration, and performance on neurocognitive tasks [15]. In this regard, the increase in tinnitus severity may negatively affect attentional orientation and executive control, reducing cognitive processing speed [6].…”
Section: The Impact Of Tinnitus Severity On MCI Presencementioning
confidence: 75%
“…Several previous studies have indicated the presence of cognitive impairments, including attention deficit, instant memory disorder, and inefficient learning in patients with chronic tinnitus [6,15]. Despite inconsistent results on the association of tinnitus with certain types of cognitive functions, tinnitus has been shown to have negative effects on executive or selective attention and working memory [6].…”
Section: The Impact Of Tinnitus Severity On MCI Presencementioning
confidence: 99%
See 3 more Smart Citations